2014
DOI: 10.19056/ijmdsjssmes/2014/v3i1/80670
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia and Micronutrient Deficiency in Elderly

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
2
10
2
Order By: Relevance
“…However, while postmenopausal estrogen levels decrease, there is an increase in red cell mass to levels that are similar to those in males, which makes it unreasonable to use different criteria for anemia in each gender 21,22 . In our study 380(39.92%) were males and 572(60.08%) were females, which was higher than other studies like in the Kaur et al 23 and Nasrin A. Qureshi et al 24 , where there was no statistical difference in both gender, and in contrast to the Chul won choi et al study in which 11.4% were males and 2.1% were females 25 . In our study Microcytic hypochromic anemia 56.05% (male) and 50.35% (female) is the predominant type of anemia as seen in Gerardo et al studies 26 , Nasrin A. Qureshi et al and S Patel et al 27 study in which microcytic hypochromic anemia was seen in 72%.This finding was in contrast to the Kaur et al 23 in which normocytic normochromic anemia is the predominant type, 56%.…”
Section: Discussioncontrasting
confidence: 67%
“…However, while postmenopausal estrogen levels decrease, there is an increase in red cell mass to levels that are similar to those in males, which makes it unreasonable to use different criteria for anemia in each gender 21,22 . In our study 380(39.92%) were males and 572(60.08%) were females, which was higher than other studies like in the Kaur et al 23 and Nasrin A. Qureshi et al 24 , where there was no statistical difference in both gender, and in contrast to the Chul won choi et al study in which 11.4% were males and 2.1% were females 25 . In our study Microcytic hypochromic anemia 56.05% (male) and 50.35% (female) is the predominant type of anemia as seen in Gerardo et al studies 26 , Nasrin A. Qureshi et al and S Patel et al 27 study in which microcytic hypochromic anemia was seen in 72%.This finding was in contrast to the Kaur et al 23 in which normocytic normochromic anemia is the predominant type, 56%.…”
Section: Discussioncontrasting
confidence: 67%
“…Moreover, it affects quality of life as well as the morbidity and mortality due to anaemia, it is considerably increased in recent times. [3,4,5,6] Fortunately, anaemia can be easily treated with drugs if identified earlier. Many at times that will be an incidental findings after a laboratory evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Literature review reveals that prevalence of anaemia increases with age and that too females under 75 years were commonly affected compared to males. [6] In India, the prevalence rate is 17.7% to 89% in different states. [4] It is high (71%) in North India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reena kouli et al [11], who reported 39.92% males and 60.08% females. However, other studies showed no statistical difference between both genders [12,13]. This is in contrast with the study conducted by Chul won choi et al [14].…”
Section: This Is In Accordance With the Study Conducted Bymentioning
confidence: 74%